Creating an Enabling Environment for Lifelong Learning in Tanzania: Lessons to be Learnt from the British System - Godfrey Michael, Muhangwa (Progress in Language, Literature and Education Research Vol. 8, 2024)
Explores the idea of creating an enabling environment for lifelong learning in Tanzania, using valuable insights from the British education system. Lifelong learning is increasingly recognized as an important factor in promoting people's adaptability and resilience in an ever-changing global landscape. Explores the key elements of the British system that foster the cultivation of a culture of lifelong learning and assesses their applicability and possible adaptation to the Tanzanian context. These elements help create an environment where learning goes beyond formal education and embraces a lifelong approach. The impact of this research includes informing education policymakers, institutions and stakeholders in Tanzania about effective strategies to create an environment conducive to lifelong learning. By recognizing the lessons of the British system and considering their adaptation, Tanzania may be able to improve its educational framework to better prepare people for lifelong learning.